Colonial Essentialism in Lord Lugard’s “The Dual Mandate”, a Critical Textual Analysis - Bello, Umar (Advances in Social Sciences Research Journal, 2017)
The Dual Mandate in British Tropical Africa is a book written by Sir Fredrick Lugard (the first colonial Governor General of Nigeria). It forms or constructs the theoretical justification of the colonial occupation of Africa and argues about ways for its effective political control. The book grounds the philosophy and ideology of the British Empire and justify its conquests and administrative style. The elaborate justifications contained in the text, this paper argues, are made on the backdrop of purely essentialist ontology that seeks to dehumanize the subaltern and raise the status of the colonialists in Africa. The dual mandate of the British Empire, according to Lugard, is to open up Africa to the civilized world and at the same time open the African mind to civilization. The mandate itself positions a binary (or social roles) involving a civilizer and one to be civilized. Lexical and syntactical analyses are done here to capture this paternalistic and racially superior philosophy. Lugard constructs his medium and perception of the other to a state of apparent objectivity using (assumptions of) the suzerainty of his gaze, the use of the ethnographic present tense and categorical modality. These make his views appear authoritative, objective and his mission legitimated. Using this authoritativeness, the subaltern is naturalized, infantilized, distanced, fetishisized and conveniently othered as an object to be mastered and used. The data is analyzed using critical discourse analysis to demystify and unravel the mask of objectivity and the ideological significance of the style involved in the text. Keyword: colonialism, subaltern, imperium, essentialism, critical discourse analysis, imperialism, lexical analysis, civilization, racism, postcolonial theory.